Analysis of Illegal Sand Mining According to the Syāfi`I School of Fiqh (Case Study of Hamlet III, Pertumbukan Village, Wampu District, Langkat Regency) - Delta Rika Wijaya; Ahmad Zuhri Rangkuti (Fox Justi : Jurnal Ilmu Hukum, 2025)
Sand mining activities in Dusun Tiga, Pertumbukan Village, Wampu District, Langkat Regency, are increasing day by day due to the high demand for materials to support both personal and regional development. However, this activity has led to significant environmental damage, primarily due to a lack of awareness and consideration in planning, operating, and managing post mining impacts. This study, which employs a field research method with both normative ( sharia ) and sociological approaches, aims to analyze the situation based on the perspective of the Shafi'i school of jurisprudence, emphasizing the importance of environmental preservation. Data were collected through observation, interviews, documentation, and literature review, and were processed through data reduction, presentation, and conclusion drawing. The findings show that illegal sand mining has caused various negative impacts, including damage to local agriculture, road infrastructure, and the overall ecosystem, while also affecting the social and economic well being of the community. To mitigate this environmental degradation, the application of Shafi'i jurisprudence is deemed crucial, as it is provides guidance, boundaries, and ethical principles for Muslims in response to and prevent further environmental harm, ultimately aiming for the welfare of the people.